The Evaluation of Home Visit Program: A Reinforcement of Character Education - Nurul Aisyah; Okada Ruli Sutoro; Tumin Tumin (Al-Hayat: Journal of Islamic Education, 2020)
This study aims to determine how the evaluation of the Home Visit Program as a reinforcement of character education in SMK (Vocational School). This study uses a qualitative method with CIPP model. The subjects of this study were taken from the Guidance dan Counseling coordinator, students, and school principal in SMK. Data collection techniques used the method of observation, interviews, and documentation. The method of observation in this study used a participatory method. Data analyze used data reduction, data presentation, drawing data conclusions. The results show that: (1) in terms of context ,only three components were applied, and one was not implemented optimally. The components are background, specific goals, and program development (2) in terms of input, it is quite good, consisting of the target components of the program, the elements involved, and the role of the teachers (3) in terms of process, that of the five components, and only three are of good value. While the other two are of less value. The components which include material, methods, obstacles, and how evaluates the system evaluates to develop character values are quite well. While the method of implementing programs and efforts to develop character values are less good (4) in terms of product, the two components are good enough. The components consist of program achievements and program evaluations.